2020
DOI: 10.1021/acscatal.0c03033
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Characterization of the Carbonylated A-Cluster in Carbon Monoxide Dehydrogenase/Acetyl-CoA Synthase

Abstract: The Wood–Ljungdahl pathway allows for autotrophic bacterial growth on carbon dioxide, with the last step in acetyl-CoA synthesis catalyzed by the bifunctional enzyme carbon monoxide dehydrogenase/acetyl-CoA synthase (CODH/ACS). ACS uses a complex Ni–Fe–S metallocluster termed the A-cluster to assemble acetyl-CoA from carbon monoxide, a methyl moiety and coenzyme A. Here, we report the crystal structure of CODH/ACS from Moorella thermoacetica with substrate carbon monoxide bound at the A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 35 publications
0
38
1
Order By: Relevance
“…Similar values can be seen in the calculations (Table 3) although these distances are slightly longer for the formate and hydroxyl ligands. At the same time, it can be found that the Ni p -Fe1 distance is very small (2.243 Å) in the PDB ID: 6YTT crystal structure [46] where there is no ligand on Ni p and in turn very long in the crystal structure PDB ID: 6X5K [36] with the carbonyl ligand. This is not the case in the EXAFS results for the CO ligand, where this distance is equal to 2.80 Å [56] (Table 2).…”
Section: Structural Propertiesmentioning
confidence: 96%
See 3 more Smart Citations
“…Similar values can be seen in the calculations (Table 3) although these distances are slightly longer for the formate and hydroxyl ligands. At the same time, it can be found that the Ni p -Fe1 distance is very small (2.243 Å) in the PDB ID: 6YTT crystal structure [46] where there is no ligand on Ni p and in turn very long in the crystal structure PDB ID: 6X5K [36] with the carbonyl ligand. This is not the case in the EXAFS results for the CO ligand, where this distance is equal to 2.80 Å [56] (Table 2).…”
Section: Structural Propertiesmentioning
confidence: 96%
“…It also would be prone to oxidation and would be unstable in biological environment. A red1 was observed experimentally, it can be formed as the product of Fe 4 S 2+ 4 Ni + p CO photolysis and it binds back CO very quickly [36]. The direct presence of Fe 4 S + 4 Ni + p in the catalytic reaction has not been proven.…”
Section: Energetics Of Methylation and Carbonylation Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the architecture of Dv HCP and Dd HCP is similar to that of the subunit of Ni, Fe‐containing carbon monoxide dehydrogenases (Ni, Fe‐CODHs) [31–38], despite the low sequence identity (15–18%) of HCPs with Ni, Fe‐CODHs. Therefore, comparisons of the three‐dimensional structures of HCPs and Ni, Fe‐CODHs are necessary to elucidate their structural evolution and functional diversities [39].…”
Section: Introductionmentioning
confidence: 99%